Solubility Enhancement of Ethyl AcetateFraction of The Artocarpus altilis (Parkinson) Fosberg Leaves with Addition of β-Cyclodextrin-HPMC by Using Kneading Method - Sabrina Sabrina; Yuni Anggraeni; Berti Puspitasaril; LBS Kardono (Jurnal Kimia Valensi, 2014)
Abstract Ethyl acetate fraction of the Artocarpus altilis (Parkinson) Fosberg extract have a potency to treat the cardiovascular diseases have poorly solubility in water. The purpose of this study was to improve the solubility of the extract. One of method to improve the solubility of the extract by mixing with cyclodextrin polymers and their derivatives. Hydroxyl propyl methylcellulose (HPMC) as a water-soluble polymer can enhance the β-cyclodextrin (β-CD) activity. Three comparisons extract and ß-cyclodextrin were: 1:2, 1:4, and 1:6 by mixing with the addition hydroxyl propyl methylcellulose 0.12%of the total weight of extract and β-CD for each formula. The sample was prepared by kneading method. The sample characterization was used Karl Fischer titration, Scanning Electron Microscopy and solubility study.Content of total flavonoid from the extract was 32.7%. The Result showed that the addition polymer combination of β-CD + HPMC caused increasing the solubility of extract in water7.04% (F1), 19.47% (F2) and 59.92% (F3) compared to extract control with significant differences at level of confidence 95% (p ≤ 0.05). Keywords : ethyl acetate fraction of breadfruit, kneading method, β-cyclodextryn, hydroxy propyl methylcellulose, total flavonoid